Classifying Universities in Turkey by Hierarchical Cluster Analysis - Erdogmus, Nihat; Esen, Murat (TURKISH EDUCATION ASSOC, 2016)
Classifying universities is regarded as an efficient strategy for developing institution-based policy for different types of universities. In Turkey, there is no widely accepted classification or official classification of universities for researchers and policy makers. Regarding this need, the first purpose of this study is to classify universities in Turkey on the basis of institutional size and performance. Since the focus of the study is institutional size and performance, researchers approach the subject from the perspectives of management and organization. Universities were classified using hierarchical cluster analysis. All state and foundation universities were included in the study. The data sources were statistics of the Council of Higher Education (CoHE), ranking lists, University Ranking by Academic Performance (URAP), Ranking of the Entrepreneurial and Innovative University Index (TUBITAK), strategic plans and annual reports of higher education institutions, and related data on research and publications. Universities were clustured on the basis of objective data not predetermined criteria. The main variables for cluster analysis were quantitative measures, ranking scores, and measures of the quality of teaching and research for each university. The results of the duster analysis showed that clustering universities by institutional size and performance as two separate variables provided better results. The scale and tenure of universities differentiated them in terms of institutional size and performance variables. Universities founded in the same years were divided into two clusters, mainly according to the size of their vocational schools. It was also found that when publication performance was expressed, those universities that were small/medium sized, focused, and long tenured were separate from other universities.
Keywords: Higher education; University; Cluster analysis; Rankings; Performance measurement in higher education; HIGHER-EDUCATION INSTITUTIONS; RESEARCH PERFORMANCE; RANKING; Education & Educational Research